Batteries: Gas Pickering Emulsion Templated Hollow Carbon for High Rate Performance Lithium Sulfur Batteries (Adv. Funct. Mater. 46/2016). (12th December 2016) - Li, Matthew; Zhang, Yining; Wang, Xiaolei; Ahn, Wook; Jiang, Gaopeng; Feng, Kun; Lui, Gregory; Chen, Zhongwei
Abstract : Nitrogen doped hollow porous carbon can be obtained using in situ generated CO2 gas bubbles, stabilized via a Pickering emulsion, as template, as describes by Z. W. Chen and co‐workers on page 8408. When applied to a lithium sulfur battery, this material demonstrates stable cycling and high discharge rate. Upon further testing, interesting mass transfer mechanics are revealed.